Designing with Medium: Exploring the Agency of Representational Media in Architectural Design - Gülle, Alper; Uluoğlu, Belkıs (Enquiry The ARCC Journal for Architectural Research, 2025)
This study attempts to elucidate the relative impact of the designated representational medium on architectural design knowledge during design activity by focusing on the relation between designers' cognitive processes and revealed design information corresponding to different representational media during the design process. The assertion here is that designing, specifically the act of representation, occurs absolutely with the existence of a medium and that representational media have agency, which affects the information content of the designers during design activity. Designing is defined as a process of construction of representations, where the act of representing facilitates a reflective dialogue between the designer and the object of representation. The framework of the study is aimed at revealing the agency of representational media through a community of practice within the shared sociocultural, and environmental contexts. The interaction between the designer and the media of representation has been structured upon the theoretical model -Activity Theory-, which offers a framework for analyzing human actions oriented toward specific purposes through instruments within particular conditions. Within the framework of the article, two workshop sessions and semi-structured interviews related to the sessions were conducted. The data derived from the interviews are examined using the reflexive thematic analysis method; information content related to various representational media within the common sociocultural and environmental context are revealed.